Petrosains RBTX Challenge 2023 empowers robotics enthusiasts in Pahang - Nurul Hazlina, Noordin (2023)
PEKAN, 18 June 2023 – The excitement of robotics filled the air as Petrosains, in collaboration with the Sports and Arts Education Division, Ministry of Education, Malaysia, organised the highly anticipated Petrosains RBTX Challenge 2023.